(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2015)
This Paper investigates the impact of currency devaluation on Pakistans Economy. The Devaluation occurs in terms of all other currencies, but it is best illustrated in the case of only one other currency. Any rising of the prices of such inputs through devaluation, would raise industrial costs and reduce the intensity of capacity utilization.It examines that currency devaluation has positioned Pakistan lose heavily both as seller and as a buyer and has made no good substitute for remedial changes in economic policies and developmental planning.In Pakistan, industries are heavily dependent on imported raw materials for industrial goods and capital goods and components, and their access to advanced countries is blocked by quotas and tariffs. , any rising of the prices of such inputs through devaluation, would raise industrial costs and reduce the intensity of capacity utilization.So, by examining devaluation in Pakistan it is concluded that it has always led us to the cost push inflation and never ending cruel economic circle.There are so many solutions to resolve the currency devaluation as appreciate the currency through Foreign Direct Investment, increase the export of goods in this situation will lead to high cash inflows because there would be high demand push by the countries.